Edward A. Tenenbaum and the Deutschmark How an American Jew Became the Father of Germanys Postwar Economic Revival - Holtfrerich, Carl-Ludwig (Cambridge Cambridge University Press, 2024)
1. Introduction; 2. Ludwig Erhard, who took credit for Edward A. Tenenbaum's success; 3. Edward A. Tenenbaum's family roots, adolescence, and military experience until 1946; 4. In action for OMGUS and currency reform in Germany 1946-1948; 5. From OMGUS to civil service in Washington DC and for Europe 1948-1953; 6. Life and fate as a business and family man 1953-1975 and beyond; 7. Conclusion.
E-Book / Zugriff nur im Lesesaal